Enhancing high-temperature chloride molten salts corrosion resistance of 310S steel with Si-added Ni–Al coating - Shipeng Xu; Faqi Zhan; Lei Wan; Yuehong Zheng; Peiqing La (Journal of Materials Research and Technology)
Ni–Al based coating is one of the common high temperature and corrosion resistant protective coatings. In the present paper, the effect of Si content on the formation of Al2O3 layer and the corrosion resistance of Ni–Al coating to chloride molten salt was studied. The research results show that the Ni–Al coatings with varying Si content mainly form NiAl2O4 and Al2O3 oxide layers after pre-oxidation, and form a three-layer structure after molten salt corrosion. The appropriate amount of Si added to the Ni–Al coating can promote the formation of the α-Al2O3 layer during pre-oxidation and thermal corrosion, improving the corrosion resistance of the coating to high temperature chloride molten salt, and hindering the diffusion of Cr elements. Particularly, the Ni–Al coating with Si content of 1.2 at.% has the thickest and densest Al2O3 protective layer, showing the best corrosion resistance. The simulation results shows that compared with the Ni–Al coating without Si, the Cl atoms in the Si-added Ni–Al coating need to overcome greater energy barriers to diffusion during the molten salt corrosion process, which also indicates that the addition of Si can improve the corrosion resistance of the coating.